Acute Rejection in the Modern Lung Transplant Era - Renaud-Picard, Benjamin; Koutsokera, Angela; Cabanero, Michael; Martinu, Tereza (Seminars in Respiratory and Critical Care Medicine, 2021)
Acute cellular rejection (ACR) remains a common complication after lung transplantation. Mortality directly related to ACR is low and most patients respond to first-line immunosuppressive treatment. However, a subset of patients may develop refractory or recurrent ACR leading to an accelerated lung function decline and ultimately chronic lung allograft dysfunction. Infectious complications associated with the intensification of immunosuppression can also negatively impact long-term survival. In this review, we summarize the most recent evidence on the mechanisms, risk factors, diagnosis, treatment, and prognosis of ACR. We specifically focus on novel, promising biomarkers which are under investigation for their potential to improve the diagnostic performance of transbronchial biopsies. Finally, for each topic, we highlight current gaps in knowledge and areas for future research.
Keywords: lung transplantation; acute rejection; cellular rejection; transplant immunology